2022
DOI: 10.1186/s12889-022-14616-5
|View full text |Cite
|
Sign up to set email alerts
|

Men’s conceptualization of gender-based violence directed to women in Alexandra Township, Johannesburg, South Africa

Abstract: Background Gender-based violence (GBV) is a crucial global public health challenge disenfranchising women and girls from enjoying their fundamental human rights, thereby threatening their well-being. While the concept of GBV does not imply that violence is always unidirectional, literature shows that women and girls are the most common victims of this type of violence. One in three women, globally, have suffered physical or sexual violence by an intimate partner or non-partner. Evidence has sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Adams et al (2013) argue that SH involves power imbalance and gender inequality. Consequently, women seem incapable of escaping from the clashes of SH due to existing social and gender inequalities and societal norms that perpetuate violence against women (Adams et al, 2013; Zinyemba and Hlongwana, 2022). In the McGregor case , the court held as followsSexual harassment occurs at the intersection of gender and power, producing a potent stench of subordination, disempowerment and inequality that so seeps through the fabric of our society that it stains its core (McGregor case para 47).…”
Section: Factors That Exacerbate Sexual Harassment As a Gendered Harm...mentioning
confidence: 99%
See 2 more Smart Citations
“…Adams et al (2013) argue that SH involves power imbalance and gender inequality. Consequently, women seem incapable of escaping from the clashes of SH due to existing social and gender inequalities and societal norms that perpetuate violence against women (Adams et al, 2013; Zinyemba and Hlongwana, 2022). In the McGregor case , the court held as followsSexual harassment occurs at the intersection of gender and power, producing a potent stench of subordination, disempowerment and inequality that so seeps through the fabric of our society that it stains its core (McGregor case para 47).…”
Section: Factors That Exacerbate Sexual Harassment As a Gendered Harm...mentioning
confidence: 99%
“…Flowing from this, it is not surprising that SH is made up of three vital dimensions as seen above namely; gender harassment, unwanted sexual attention and sexual coercion (Burn, 2019; Fitzgerald et al, 1995: 430–432). These factors inform the prevailing power inequalities within gender relations that frequently favour men and thus enable patriarchal attitudes (Zinyemba and Hlongwana, 2022). Therefore, SH as a form of gender discrimination is underpinned by the sexist ideology of male dominance and male superiority (Adams et al, 2013: 1153).…”
Section: Factors That Exacerbate Sexual Harassment As a Gendered Harm...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, women are placed in subordinate positions and are expected to comply or face punishment. Zinyemba and Hlongwana (2022) argue that sociocultural norms tend to favor uneven gender power relations, resulting in disadvantages for women, thus illustrating women's susceptibility to gendered violence.…”
Section: Physical Violencementioning
confidence: 99%
“…Research by Douglas & Hines (2011), revealed that a number of men who have reached out to domestic abuse hotlines or agencies experienced a variety of negative responses like agencies only help women and men were ignored and treated as perpetrators. Male victims who experience such type of unfair treatment are most likely not going to report future cases of violence and intensify their feelings of helplessness, isolation and nowhere to go for support (Zinyemba & Hlongwana, 2022). Furthermore, throughout history a good number of work that surrounds exploring men's experiences in abusive situations have always tilted towards the influence that it has on impairing societal expectations and the stereotypes surrounding masculinity as being important (Malik & Nadda, 2019;Yagi et al, 2022).…”
Section: Attitudes Of Male Victims Of Violencementioning
confidence: 99%